Protein Kasar Plasma Seminalis Sapi Menurunkan Kejadian Nekrosis Spermatozoa Kambing yang Disimpan pada Suhu Dingin (BULL SEMINAL PLASMACRUDE PROTEIN DECREASING THE PERCENTAGE OF NECROSISIN GOATSPERMATOZOA THAT KEPT IN COLD TEMPARATURE) - Susilowati, Suherni; ., Hardijanto; Triana, Indah Norma (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
The aim of this study was to determine the benefits of bullseminal plasma crude proteinin goatspermatozoa diluent to improve of frozen semen quality.This study consists of three treatments: (i)treatmentcontrol (P0,goat semen + diluents ; (ii) treatment I(PI, diluent + goat semen + bull seminal plasmacrudeprotein (1:1);and (iii)treatment II (PII, diluent + goat semen+ bull seminal plasma crude protein (1:2). Alltreatments were kept in arefrigerator (5oC) andobserved for necrosis of goatspermatozoa, daily. The highestspermatozoa necrosis was observed in the diluter without the bull seminal plasma crude protein eitheratday1, 2, 3, 4orday 5. The necrosis was statistically significant different (p<0,05) between P0, PI and PII.withthe lowest percentagenecrosis at PI. In conclusion, the addition of bull seminal plasma crude proteinin skim milk diluentwill decrease theincidenceof necrosis ingoat spermatozoa which were kept in coldtemperature.
Keywords: crude protein plasma seminalis; bull’s; necrosis; goat’s spermatozoa